EP120/#1082 Compare the surgical outcomes of robotic versus laparoscopic surgery in the treatment of endometrial cancer for morbidly obese patients. (4th December 2022) - Lim, Peter; Kennedy, Lauren; Mcmurray, Keanu; Siddiqui, Fawaaz
Abstract : Objectives: Compare the surgical outcomes of robotic versus laparoscopic surgery in the treatment of endometrial cancer for morbidly obese patients. Methods: A prospective analysis of obese patients who underwent robotic assisted hysterectomy with lymphadenectomy (RHLND) was compared to patients who underwent a total laparoscopic hysterectomy with lymphadenectomy (LHLND) for treatment of endometrial cancer. Estimated blood loss (EBL), operative times, intraoperative and postoperative outcomes, number of pelvic (PLN) and paraaortic (PALN) lymph nodes retrieved and rate of conversion to open laparotomy were analyzed. Fisher Exact tests or two tailed t-tests was performed to evaluate for difference. Results: Total of 330 patients underwent minimally invasive surgical treatment for endometrial cancer between 1999–2019. 254 (77%) patients underwent RHLND and 76(23%) underwent LHNLND. The mean age and BMI were similar. RHLND average operative time (123 minutes) vs LHLND (169 minutes) and RHLND EBL (50cc) vs LHLND EBL (198cc) was less. However, the average number of PLN (18) and PALN (9) in RHLND was found to be significantly less than LHLND PLN (24) and PALN (17). The rate of conversion was less for RHLND (0%) and LHLND (7/76) (9.2%) group. No difference in postoperative 17/254 (7%) RHLND vs 4/76 ( 5%) LHNLND and intraoperative complication rate 5/254 (2%) for RHLND vs 2/76 (3%) LHLND respectively. Conclusions: Surgical outcomes for treatment of endometrial cancer in obese patients with RHLND compared to LHLND is associated with less blood loss, shorter operative time, less conversion to open laparotomy with no difference in rate of intraoperative and postoperative complication.